Risks of a slow-motion EMU reform - László Andor (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2019)
The article provides a critical assessment of how the Economic and Monetary Union was designed, implemented and reformed in the European Union and discusses the risks of a slow-motion reform process. It is argued that the fact that the euro area economy has recovered in the last few years has become a source of complacency and delays. In particular, powerful forces continue to downplay the importance of systemic reconstruction and the risk of disintegration remains high despite the relative tranquillity of markets in the 2014–2018 period. Finally, the article evaluates competing paradigms about the eurozone crisis and the pros and cons of fiscal capacity building.
Keywords: E63; F45; 330; European Union; Great Recession; eurozone crisis; divergence; EMUreform; fiscal capacity